Microwave Performance, Microstructure, and Crystallization of (Mg0.6Zn0.4)1−yNiyTiO3 Ilmenite Ceramics - Chun-Hsu Shen; Chung-Long Pan; Shih-Hung Lin; Cheng-Che Ho (Applied Sciences, 2021)
The sintering behavior, microstructure analysis, crystallization, and microwave performance of (Mg0.6Zn0.4)1−yNiyTiO3 (y = 0.01–0.2) ceramics, processed with raw powders of MgO, NiO, ZnO, and TiO2 via the conventional solid-state method, are investigated. The main phases of (Mg0.6Zn0.4)1−yNiyTiO3 ceramics were obtained. With partial replacement by Ni2+, the (Mg0.6Zn0.4)0.95Ni0.05TiO3 could be well sintered at 1200 °C, and the microwave performance was shown to be positively correlated with sintering temperature. The permittivity (εr) saturated at 18.7–19.3, and the quality factor (Qf) values approached 72,000–165,000 (GHz) as the sintering temperatures increase from 1125 to 1250 °C. The temperature coefficient of resonance frequency (τf) falls in a stable range of −62.9 to −66 ppm/°C as sintering temperature rising. A permittivity (εr) of 19.3, a maximum Qf value of 165,000 (GHz), and a temperature coefficient (τf) of −65.4 ppm/°C were measured for the samples at 1200 °C/4 h. (Mg0.6Zn0.4)0.95Ni0.05TiO3 material system shows high potential for applications of high frequency-selection components in satellite communication and 5G wireless telecommunication systems.